2020
DOI: 10.1016/j.corsci.2020.108820
|View full text |Cite
|
Sign up to set email alerts
|

Metal dusting of Inconel 625 obtained by laser beam melting: Effect of manufacturing process and hot isostatic pressure treatment

Abstract: Metal dusting resistance of Inconel 625 alloy obtained by laser beam melting (LBM), compared to wrought alloy 625 was assessed during 9 500 h at 610°C. Whatever the manufacturing process, the mass variations were very small when the systems were ground thanks to the formation of a uniform protective chromia layer. However, the high surface roughness was shown to be detrimental as the waviness favoured the local formation of an unprotective spinel oxide. Hot isostatic pressure (HIP) treatment recrystallized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…4 . This increase in reactivity is transient and not necessarily detrimental to the part in terms of affected thickness, as has been seen in high-temperature oxidation of alloy 718, 4 but may lead to local breakaway, as observed on alloy 625 23,34 or Hastelloy X. 33 3.…”
Section: Summary Of Am Alloy Performance and Conclusionmentioning
confidence: 82%
See 1 more Smart Citation
“…4 . This increase in reactivity is transient and not necessarily detrimental to the part in terms of affected thickness, as has been seen in high-temperature oxidation of alloy 718, 4 but may lead to local breakaway, as observed on alloy 625 23,34 or Hastelloy X. 33 3.…”
Section: Summary Of Am Alloy Performance and Conclusionmentioning
confidence: 82%
“…However, sometimes, the surface geometry can affect the nature, the kinetics, and the growth constraints of the layer and its adherence. In an atmosphere of catastrophic powdery carburization, called metal dusting, Vernouillet et al 34 showed that the samples of alloy 625 LBM and LBM + HIP with rough surfaces, suffered greater mass losses than polished samples. In addition, the raw HIP samples showed large variations in behavior.…”
Section: Effect Of Surface Roughnessmentioning
confidence: 99%